Actuator elements insertion tool for pressure pipeline - Anasiewicz, Kamil; Kowalska, Beata; Kowalski, Dariusz; Suchorab, Paweł (Instal, 2021)
The article presents a concept and a prototype of a tool enabling the insertion of actuator elements into water supply pipelines working under pressure. The tool was initially developed as a device for removing ice plugs in pipelines. The construction of the prototype showed its much greater versatility. The result was a platform enabling the insertion of samplers directly in the water stream flowing through the pipeline, pressure and flow rate sensors location in this stream, sediment, biofilm collection from the walls of the pipeline and dosage of disinfectant, e.g. chlorine, into the working pipelines. In assumptions, the tool can work with commonly used devices for drilling pipelines, as well as with some types of fire hydrants. The article describes the concept of the tool, the construction of its prototype and an initial laboratory experiment involving the use of a tool to remove an ice plug in a fragment of a water pipe.